Microcontroller based food dehydrator for Rengginang crackers micro businesses in Prambontergayang Village, Tuban District - Eko Wahyu Abryandoko; Faisal Ashari; Nungki Dio Febriansa; Ary Angga Fachreza (University of Merdeka Malang, 2024)
The micro-business of Rengginang crackers with the Urnika brand in Prambontergayang Village, Tuban District, is an industry in the food sector. The process of drying Rengginang crackers inÂ partnerâ€™s still uses conventional methods or under sunlight to carry out the drying process. Hence, it takes quite a long time to dry Rengginang, namely around 6-7 days. This community service program aims to develop and train the use of alternative technology for drying Rengginang crackers to Rengginang crackers micro-entrepreneurs in Prambontergayang Village, Tuban District. The method used for implementing PKM is a participatory approach (participatory action research/PAR). The results of the PKM carried out have had a positive impact on partners, namely more optimal and efficient drying. Drying using a microcontroller-based food dehydrator can speed up drying up to 120 minutes with a capacity of 5000 pcs of wet Rengginang. With this technology, partners can increase their production capacity for Rengginang crackers so that they can increase the expected number of sales.